HUBUNGAN DURASI PEMBERIAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING PADA ANAK - Nurkarimah Nurkarimah; Oswati Hasanah; Bayhakki Bayhakki (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Stunting is the short and very short state of body shown with the z-score height for age less than -2 SD due to accumulated lack of nutrients from pregnancy to 24 months. Stunting becomes a health problem to be overcome because it deals with an increased risk of morbidity, mortality, delayed motor development, and retardation of mental growth children. The purpose of this research was to determine the relationship between the duration of exclusive breastfeeding with incidence of stunting in children aged 6  24 months in Rejosari Pekanbaru Health Center with correlation research design and cross-sectional approach. Population consists of 681 children, samples consists of 87 children taken by accidental sampling technique based on inclusions criteria: children age 6  24 month, living in work area Rejosari Health Center, and children’s mother gives permit to become respondent. Univariate analysis showed that stunting children were 37,9% with the most respondents were 54% men, the majority of children had normal birth weight of 87,4%; most of the mother respondents were educated at senior high school 63,2%; the majority of mothers were housewives 89,7%; and most of them were 31% minang ethnic. Bivariate analysis using Mann-Whitney obtained p value (0,000) <α (0,05), so it can be concluded there is correlation between exclusive breastfeeding duration and stunting incidence in children aged 6  24 months in work area of Rejosari Pekanbaru Health Center. Based on this research it is advisable for mothers to breastfeed exclusively as recommended by WHO for 6 months in infants to achieve optimal growth. Keywords: Exclusive Breastfeeding, Exclusive breastfeeding duration, Stunting